(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Linear discriminant analysis is necessary to investigate the environment of deposition of sediment or transport. 14 samples [from locations A1, A2, OL1, OL2, O1, O2, AG1, AG2, A3, A4, AG3, AG4, O3 and O4] were taken from four villages in Kwara state for the study. Textural parameters were first investigated from the result of grain size analysis performed using German standard sieve set of mesh with shaker. These results enhanced the determination of critical shear stress as well as linear discriminant analysis. The critical shear stress accounts for sediment transport and deposition including their environments, the following results were obtained: The critical shear stress ranges from 0.33Nm-2 to 1.31Nm-2. The highest value (1.31065877 Nm-2) is observed in OL2 and the lowest (0.32766469 Nm-2) is from the environments of A3 and O4. The stress which rolls or actually transports the particle varies within 0.1 Nm-2 to 0.3 Nm-2 except in OL2 and AG3 environments whose value is approximately 0.4. The linear discriminant analysis shows that the dregs were deposited by collective effects of marine, as well as those of fluvial activities due to the influence of turbidity in the beach environment. The multivariant discriminant plot confirms strongly, the environment of deposition as beach in this region.